An approach to Financial Education related with teaching practice in 3rd grade of High School - Navarro, Gabriela Ferreira Gonçalves; Silva, Jhone Caldeira (Educação Matemática Debate, 2023)
Financial Education involves acquiring knowledge, skills, and attitudes that empower individuals to make informed decisions regarding managing financial resources. In this context, we present an approach to this topic related to teaching practice with senior high school students. The goal is to emphasize the importance of Financial Education in students' lives based on the content of financial mathematics teaching. The method included lectures and interactive activities covering different topics, such as distinguishing between needs and wants, creating budgets, and understanding simple and compound interests. The results indicated that students absorbed theory and applied the knowledge in practice, demonstrating increased financial awareness and the ability to make informed decisions.